Research on the feasible of the pen-hold four-side-attack and its technical characteristic - Chen, J.; Cai, J. (2001)
With the development of the table tennis sport, creation are becoming more and more important. Creation means development. Only the creation can make the sport vital. For few decades, table tennis sport in China has been on the top of the world, one of the important reasons is that Chinese players have always been at the forefront of the technical creation. The "four-side-attack" racket try to enrich and develop the Chinese traditional pen-hold grip fast attack. Many pupils in Beijing and Shunyi county have been trained to play table tennis with this racket. Some of them have already made great progress. In this thesis, we adopt the methods from document researching, expert visiting, experiment analysis and matches statistics to test the speed, the spin and the power of the forehand reverse attack. We have obtained the following conclusions after experiments and analysis: 1.The "four-side-attack" racket can be used with four sides, with own functions in each side. In the point of speed, spin and power, it is little difference between traditional rackets. So, if only scientific train methods be adopted can this racket be feasible. 2. The speed of the forehand front is faster than forehand reverse. The reason is that when using reverse side, the angle of the wrist turns outside which will affects the speed. So, forehand front is suitable for smashing. 3. The spin of the forehand reverse is stronger than forehand front, and forehand reverse has clear side-spin, that come the result that forehand reverse is more suitable for loop drive. 4. In the point of power, there is no difference between forehand front and forehand reverse. 5. The "four-side-attack" racket has clear superiority in service. But the players must improve the skill of receive and raise the percentage of hits after service. 6.With the ability of stalemate, "four-side-attack" racket can contend with the traditional rackets. But it must strengthen the ability and consciousness of the active attack of backhand, bring the power of two-side of backhand into full play.